Closing gender gaps in developing countries: Impacts on poverty, diets and food security - Thurlow, James; Levy, Stephanie (International Food Policy Research Institute, 2023)
Women earn less than men, not only in agriculture, but across the broader agri-food system. Recent analyses by the World Bank found that, in Ethiopia and Nigeria, women working in agriculture earn a third less than men, with even larger gender gaps outside agriculture. This is partly due to discrimination in the workplace, but also women’s more-limited access to productive resources, including education and finance. The CGIAR Foresight initiative and the World Bank’s Gender Innovation Lab are using economywide models linked to household surveys to measure the impacts of closing gender-earnings gaps on national economies and agrifood systems and on household poverty, diet quality, and food security. Results from Ethiopia and Nigeria indicated that closing gender gaps in and beyond agriculture could raise national GDP by around 3% and reduce national poverty and hunger headcount rates by around 2 percentage points. This is equivalent to lifting 6 million women and men out of poverty across the two countries and reducing the risk of undernourishment for 2 million people. Benefits are not limited to women engaged in rural agriculture—the broader economy and population also benefits significantly. To our knowledge, this is the first collaboration between foresight modelers and household-impact evaluation experts to assess the broader benefits of closing gender gaps in developing countries. Our analysis provides new evidence on the importance of genderintentional policies and investments, and our modelbased approach allows for greater engagement with new decision-making audiences, such as the Ministries of Finance and Planning.